Aromatic Bromination Abolishes the Psychomotor Features and Pro-Social Responses of Mdma (“Ecstasy”) in Rats and Preserves Affinity for the Serotonin Transporter (Sert) - Hernandez-Kunstmann, A; Saez-Briones, P; Barra-Pezo, R (Frontiers Media S.A., 2019)
The entactogen MDMA (3,4-methylenedioxy-methamphetamine, “Ecstasy”) exerts its psychotropic effects acting primarily as a substrate of the serotonin transporter (SERT) to induce a non-exocytotic release of serotonin. Nevertheless, the roles of specific positions of the aromatic ring of MDMA associated with the modulation of typical entactogenic effects, using analogs derived from the MDMA template, are still not fully understood. Among many possibilities, aromatic halogenation of the phenylalkylamine moiety may favor distribution to the brain due to increased lipophilicity, and sometimes renders psychotropic substances of high affinity for their molecular targets and high potency in humans. In the present work, a new MDMA analog brominated at C(2) of the aromatic ring (2-Br-4,5-MDMA) has been synthesized and pharmacologically characterized in vitro and in vivo. First, binding competition experiments against the SERT-blocker citalopram were carried out in human platelets and compared with MDMA. Besides, its effects on platelet aggregation were performed in platelet enriched human plasma using collagen as aggregation inductor. Second, as platelets are considered an appropriate peripheral model for estimating central serotonin availability, the functional effects of 2-Br-4,5-MDMA and MDMA on ATP release during human platelet aggregation were evaluated. The results obtained showed that 2-Br-4,5-MDMA exhibits higher affinity for SERT than MDMA and fully abolishes both platelet aggregation and ATP release, resembling the pharmacological profile of citalopram. Subsequent in vivo evaluation in rats at three dose levels showed that 2-Br-4,5-MDMA lacks all key MDMA-like behavioral responses in rats, including hyperlocomotion, enhanced active avoidance conditioning responses and increased social interaction. Taken together, the results obtained are consistent with the notion that 2-Br-4,5-MDMA should not be expected to be an MDMA-like substrate of SERT, indicating that aromatic bromination at C(2) modulates the pharmacodynamic properties of the substrate MDMA, yielding a citalopram-like compound. © 2019 Sáez-Briones, Castro-Castillo, Díaz-Véliz, Valladares, Barra, Hernández and Cassels.